HEALTH AND MEDICINE PRACTICE OF THE INDIGENOUS KANDHA TRIBE IN COLONIAL ODISHA: A HISTORICAL STUDY - Kanhar, Anupama; Tripathy, Sishir Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The colloquial tribe of Kandha in Odisha had a differentiated and multifarious scheme of health and medicine closely estimated with their spiritualism beliefs, ecological understanding and social action. This paper discusses the natural laws of medicine used by the kandhas where their natural medicine is based on herbal medicines, rituals and folk medicine. This historical analysis dwells on the interplay between Kandha medicine system and colonial medical intervention using archival record, colonial report, ethnographic book, oral traditions. The results indicate that during the British colonial period, the policies to discourage the indigenous healing activities outsiders, especially the British citizens, promoted western medicines and legislature to limit its practice; however, the Kandhas remained resilient and managed to accommodate, negotiate, and even keep their indigenous knowledge intact. The paper also reveals how the discourse of colonialism constructed indigenous medicine as something superstitious and did not acknowledge its science roots. This study adds value to the wider discussion of indigenous medical history, knowledge system, and the politics/relationship of colonial power in Odisha by analyzing the response of Kandha who aggressively defied colonial rule by practicing healing strategies even during the colonial era.